Pemahaman konsep Matematika Melalui Problem Base Learning Pada Peserta Didik Kelas VIII-E SMP Negeri 1 Kenduran Tahun Pelajaran 2020/2021 - arka winardi (Postulat : Jurnal Inovasi Pendidikan Matematika, 2021)
Concept understanding is one of the mathematical skills or skills that are expected to be achieved in learning mathematics, namely by demonstrating an understanding of the mathematical concepts being learned, explaining the relationship between concepts and applying concepts or algorithms in a flexible, accurate, efficient and precise manner in problem solving. Mathematical understanding will be meaningful if mathematics learning is directed at developing the ability of mathematical connections between various ideas, understanding how mathematical ideas are interrelated so that a comprehensive understanding is built, and using mathematics in contexts outside of mathematics.Key words: understanding, understanding mathematical concepts, learning mathematics